If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8b + -1(-2b) = 0 Remove parenthesis around (-2b) -8b + -1 * -2b = 0 Multiply -1 * -2 -8b + 2b = 0 Combine like terms: -8b + 2b = -6b -6b = 0 Solving -6b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Divide each side by '-6'. b = 0 Simplifying b = 0
| 18x+5-1+8x=46 | | 9n-5=-29+3n | | p-(-11)=11 | | 4z-22=-26+8z | | -6x-32=2 | | 12=9x+3+6 | | p+1=16 | | 60x+75y=9 | | -8+n=-7 | | (-11)-w=(-36) | | 4x-3-7=-27 | | x-(-15)=10 | | 2y-20=35 | | 4x+7+2x=-5x | | -8(9k+7)=15+3k | | 6x-8x+10=9x+19+13 | | r+8=22 | | 5x+2(x-3)+2x=6x+3(x+2)-4+x | | x+y-24=0 | | 12m=240 | | -12x-2y=-54-3x | | Kx+13-8x=-1 | | -7d-2d=-33 | | -2x+3=.5x+3 | | 2x^2=7x-29 | | 17+a=8 | | 3x-7y=6-5y | | 20n=180 | | 1=X-2x^2 | | 3d=9d-9 | | 29-3c=9(7c+2) | | 6=7y+3 |